Traumatic brain injury and shaken baby syndrome. - Wellingson S Paiva; Matheus S Soares; Robson L O Amorim; A Ferreira de Andrade; Hamilton Matushita; Manoel J Teixeira (Acta Médica Portuguesa, 2011)
Shaken baby syndrome is a serious form of physical child abuse, which is frequently overlooked. It is defined as vigorous manual shaking of an infant who is being held by the extremities or shoulders, leading to whiplash-induced intracranial and intraocular bleeding and no external signs of head trauma. This syndrome is seen most commonly in children under 2 years, mainly in children under 6 months. This article summarizes issues related to clinical presentation, diagnosis, risk factors, and interventions for healthcare professionals.